Iron Deficiency Anemia in Adult Onset Still's Disease with a Serum Ferritin of 26,387 μg/L - Sheetal Patel; Seyed Monemian; Ayesha Khalid; Harvey Dosik (Anemia)
Serum ferritin rises in the anemia of chronic inflammation reflecting increased iron storage and other changes mediated by inflammation. When iron deficiency coexists, the ferritin may not always decline into the subnormal range. We describe the rare interaction of iron deficiency with the extreme hyperferritinemia characteristic of adult onset Still's disease. The combination has clinical relevance and allows deductions about the presence of serum ferritin at 26,387 μg/L despite obvious iron depletion. The diagnosis of iron deficiency anemia was delayed and became fully obvious when her Still's disease remitted and serum ferritin decreased to 6.5 μg/L. The coexistence of iron deficiency should be considered when evaluating a patient with anemia of chronic inflammation even when the ferritin level is elevated several hundredfold. Further insights on ferritin metabolism in Still's disease are suggested by the likelihood that the patient's massive hyperferritinemia in the acute phase of Still's disease was almost entirely of the iron-free apoferritin form.